Almond-shell biomass ash (ABA): A greener alternative to the use of commercial alkaline reagents in alkali-activated cement - Soriano, Lourdes; Font, Alba; Tashima, Mauro M. [UNESP]; Monzó, José; Borrachero, Maria Victoria; Bonifácio, Thaís; Payá, Jordi (Elsevier, 2021)
The use of almond-shell biomass ash (ABA) as an alternative component to the commercial reagents used in the activation of blast furnace slag (BFS) systems is investigated. The presence in its chemical composition of a high content of K2O indicates that it can alkalinize the medium. 100% waste-based mixtures ABA/BFS were studied by micro- and macrostructural tests. A compressive strength of 44 MPa was achieved by the mortar with 25% ABA addition cured for 7 days at 65 °C. The microstructural analysis showed the formation of slightly different C(K)-A-S-H gels to those formed when using KOH. The use of ABA in BFS mortars is shown as a greener alternative for construction materials because the replacement of synthetic chemical reagents that produced around a 75–80% of reduction in the values of kgCO2eq/m3 material.
Keywords: Alkali activated materials; Almond-shell biomass ash; Blast furnace slag; Eco-friendly material; Waste valorisation